Persistent low-Level viremia in persons living with HIV undertreatment: An unresolved status. Issue 1 (31st December 2021) - Crespo-Bermejo, Celia; de Arellano, Eva Ramírez; Lara-Aguilar, Violeta; Valle-Millares, Daniel; Gómez-Lus, Mª Luisa; Madrid, Ricardo; Martín-Carbonero, Luz; Briz, Verónica
ABSTRACT: Antiretroviral therapy (ART) allows suppressed viremia to reach less than 50 copies/mL in most treated persons living with HIV (PLWH). However, the existence of PLWH that show events of persistent low-level viremia (pLLV) between 50 and 1000 copies/mL and with different virological consequences have been observed. PLLV has been associated with higher virological failure (VF), viral genotype resistance, adherence difficulties and AIDS events. Moreover, some reports show that pLLV status can lead to residual immune activation and inflammation, with an increased risk of immunovirological failure and a pro-inflammatory cytokine level which can lead to a higher occurrence of non-AIDS defining events (NADEs) and other adverse clinical outcomes. Until now, however, published data have shown controversial results that hinder understanding of the true cause(s) and origin(s) of this phenomenon. Molecular mechanisms related to viral reservoir size and clonal expansion have been suggested as the possible origin of pLLV. This review aims to assess recent findings to provide a global view of the role of pLLV in PLWH and the impact this status may cause on the clinical progression of these patients.